Smartphone addiction in children: patterns of use and musculoskeletal discomfort during the COVID-19 pandemic in Iran - Hamid Reza Mokhtarinia; Maryam Heydari Torkamani; Ozra Farmani; Akbar Biglarian; Charles Philip Gabel (BMC, 2022)
Abstract Background Smartphone use has increased significantly, especially during the period of global pandemic caused by the novel SARS-CoV2 coronavirus (COVID-19). Concurrently, smartphone addiction is a growing social problem in children and adolescents with the consequence of adverse health outcomes. This study assessed the prevalence of smartphone addiction, patterns of use, and the experienced body-region discomfort among Iranian school students during the COVID-19 pandemic. Methods A cross-sectional study with students from grades 1-9 recruited n = 585 participants (mean age = 14.49 (2.26 years); female = 65.8%). Data were collected from parents and students through the online 'Smartphone addiction scale-short version' (SAS-SV), self-reported demographic questionnaires, and extracts of the Nordic musculoskeletal questionnaire for the evaluation of musculoskeletal disorders. Results The prevalence rate of smartphone addiction (53.3%) was relatively high in the overall sample. Participants spent 6.85 (4.62) hours per day on their smartphones, which had increased 53.86% relative to the pre-pandemic period. The primary smartphone uses were for social networking (77.9%), web-surfing (53.3%), and camera activities (50.9%). There was a positive correlation between smartphone addiction as assessed with the SAS-SV and daily use time (r = 0.34, p < 0.001), and the percentage of change relative to the pre-pandemic period (r = 0.26, p < 0.001). Discomfort related to smartphone use was mostly reported as present in the eyes (39.7%) and neck (39.1%). A positive correlation was found (p < 0.001) between smartphone addiction and discomfort in the eyes, neck, wrists, shoulders, and upper-back. Conclusion The more frequent usage of smartphones by students during the Covid-19 pandemic were associated predominantly with discomfort to the eyes and neck. Parents should consider the complications of musculoskeletal and postural changes during the child's future years and pay particular attention to the individual's patterns of smartphone use with an emphasis on posture and usage that reduces discomfort to the eyes and the musculoskeletal system, particularly the neck.